Pengaruh Kreativitas dan Motivasi terhadap Minat Berwirausaha Anggota Wimut (Wirausaha Muda Tulungagung) - Shinta, Imelda Ajeng Nur; Suja’i, Imam Sukwatus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to analyze the factors that influence the entrepreneurial interest of WIMUT (Young Entrepreneurs of Tulungagung) members in KOPDAR (Kopi Darat) and bazaar activities. Observations and interviews with WIMUT administrators showed low member interest in KOPDAR and bazaar activities, which resulted in a lack of inspiration, motivation, innovation, and member participation, as well as a decrease in the number of bazaar visitors. This study is expected to help overcome these problems by identifying the factors that influence the entrepreneurial interest of WIMUT members, as well as formulating strategies to increase their interest and participation in KOPDAR and bazaar activities. By increasing the entrepreneurial interest of WIMUT members, it is expected to encourage innovation, increase creativity, and maximize the potential of MSMEs in Tulungagung. The data collection method used was a questionnaire and data analysis using multiple linear regression. The results of the t-test study proved that (Creativity X1) obtained a t_count value (2.404) > t_table (2.00030) and (Motivation X2) obtained a t_count value (3.151) > t_table (2.00030) it can be concluded partially that